Experiences of living with type 2 diabetes in Pakistan: the role of culture and family in physical activity - Omama Tariq; Claire Rosten; Jörg Huber (BMC, 2022)
Abstract Background Diabetes-related guidelines recommend lifestyle changes for people living with type 2 diabetes (PLwD). In South Asian (SA) families, cultural and contextual expectations often influence people's decisions. However, broad explanations provided in the existing literature and theories concerning family involvement can increase the chance of health professionals overlooking the complexities of family roles within SA communities. Previous literature has identified the need to examine the perspectives of PLwD and their family members in Pakistan to shed light on factors perceived to support and hinder recommended physical activity (PA) to manage type 2 diabetes. This study explored (1) the enablers of and barriers to PA in the context of PLwD in Pakistan and (2) family involvement regarding PLwD's engagement with PA. Methods Semi-structured interviews were conducted with 30 PLwD and 17 family members of PLwD who were recruited in metropolitan Lahore (Pakistan) and primarily used state health services available to relatively disadvantaged populations. Interviews were transcribed and analysed using thematic analysis. Results Three themes were identified: (1) Going for a walk as a feasible PA; (2) the role of family members in influencing PA; and (3) gender differences and cultural acceptability of an activity. PA enablers for PLwD consist of gender-specific opportunities for activity facilitated by peers and family members. Culturally acceptable opportunities for PA in Pakistan for specific genders and age groups within the socio-cultural context constituted an essential factor. In this study, all women with diabetes described walking as the only acceptable form of PA, whereas some men mentioned other activities such as running, playing cricket, and cycling. Conclusions Medical guidelines must consider patients' daily routines, account for cultural and familial expectations of different genders and age groups, and address social and physical barriers encountered by these different groups to encourage PA among PLwD in SA cultures.